2010
DOI: 10.1203/pdr.0b013e3181ca0aa2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Metalloproteinase Inhibition in a Murine Model of Renal Ischemia-Reperfusion Injury

Abstract: Ischemia-reperfusion injury (IRI) is a leading cause of acute tubular necrosis and delayed graft function in transplanted organs. Upregulation of matrix metalloproteinases (MMPs) propagates the micro-inflammatory response that drives IRI. This study sought to determine the specific effects of Marimastat (Vernalis, BB-2516), a broad spectrum MMP and tumor necrosis factor-α-converting enzyme inhibitor, on IRI-induced acute tubular necrosis. Mice were pre-treated with Marimastat or methylcellulose vehicle for 4 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 45 publications
(48 reference statements)
3
30
0
1
Order By: Relevance
“…Urinary MMP-9, in combination with other markers, could serve as a biomarker of AKI (40). A wide variety of AKI models have characterized an increase in the expression of MMP-2 and MMP-9 as well as MMP-7 (8,11,91). Although methods to decrease MMP activity generally reduce injury in the majority of experimental models, at least one study shows that MMP-9 knockouts did worse, due to a diminished antiapoptotic signaling through stem cell factor (Table 2).…”
Section: Mmps In Renal Pathologymentioning
confidence: 99%
“…Urinary MMP-9, in combination with other markers, could serve as a biomarker of AKI (40). A wide variety of AKI models have characterized an increase in the expression of MMP-2 and MMP-9 as well as MMP-7 (8,11,91). Although methods to decrease MMP activity generally reduce injury in the majority of experimental models, at least one study shows that MMP-9 knockouts did worse, due to a diminished antiapoptotic signaling through stem cell factor (Table 2).…”
Section: Mmps In Renal Pathologymentioning
confidence: 99%
“…Renal injury following IRI does not improve and typically worsens over time. As an organ with high perfusion rates, the kidneys are sensitive to reperfusion following ischemia (2). Therefore, renal IRI is likely to occur following kidney transplant, kidney vascular surgery, extracorporeal shock wave lithotripsy or resuscitation (3).…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, we demonstrated that ischemic AKI induces up-regulation of matrix metalloproteinases (MMPs), which results in a proteolytic degradation of -renal microvascular matrix, with potential destruction of peritubular capillaries and subsequent worsening of acute tubular injury (ATI) [14]. Furthermore, inhibition of MMPs protected against such damage and suppressed subsequent progression of AKI, findings that have created interest in MMP inhibitors as drugs for AKI [14,15]. Recent studies, however, highlighted the beneficial roles of MMPs in tissue remodeling and/or recovery in several diseases and organ injuries, including ischemia/reperfusion injury [16,17,18,19,20].…”
Section: Introductionmentioning
confidence: 99%